Design and Analysis of Parallel Adjusting Equipment of Vertical Drilling - Zhou Bin; Zeng Yishan; Zi Bin (Jixie chuandong)
Focusing on the current limited vertical adjustment technique of large-scale drillings,a 6-DOF parallel adjustment equipment with 12 inputs is designed for the working condition of vertical drilling.The equipment mechanism consists of 6branched chains with redundancy which are symmetrical in structure.Each of the chains is composed by a compound of rotate joint and a compound of spherical joint,while the two pairs are connected by two prismatic pairs.The modal analysis is carried out on the body which is based on ANSYS software,first six order frequency distribution and modal vibration mode,and along the X、Y、Zdirection of the displacement frequency response about the moving platform are got.The analysis consequence shows that the most sensitive of external forces to the moving platform is 46 Hz frequency.Otherwise,the working space of the 6-DOF platform is obtained by using the 3-D searching algorithm.The results have significant meanings in the further research on the correlation between the parameters and the whole mechanism,as well as the optimization of the parameter.